2021
DOI: 10.1016/j.mran.2020.100116
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for sporadic cryptosporidiosis: A systematic review and meta-analysis

Abstract: Cryptosporidium spp. is an important cause of gastrointestinal disease worldwide, responsible for 69 million cases of illness in 2016. Information on the sources and transmission pathways of human cryptosporidiosis results mainly from outbreak investigations. A systematic review and a meta-analysis of case-control and cohort studies were performed to determine the main risk factors associated with sporadic cryptosporidiosis. Suitable scientific articles were identified through a systematic literature search an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…The global emission of Cryptosporidium oocysts to surface waters has been estimated at 3×10 17 oocysts per year (Hofstra et al 2013), which has been associated with high-pro le outbreaks. Cryptosporidium was estimated to be responsible for 69 million cases of illness, and 57203 deaths in 2016 (Kooh et al, 2021). During 2009 and 2017, 444 Cryptosporidiosis outbreaks occurred in US and resulted in 7465 cases, of which 56.7% were associated with contaminated river/reservoir and recreational water (Gharpure et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The global emission of Cryptosporidium oocysts to surface waters has been estimated at 3×10 17 oocysts per year (Hofstra et al 2013), which has been associated with high-pro le outbreaks. Cryptosporidium was estimated to be responsible for 69 million cases of illness, and 57203 deaths in 2016 (Kooh et al, 2021). During 2009 and 2017, 444 Cryptosporidiosis outbreaks occurred in US and resulted in 7465 cases, of which 56.7% were associated with contaminated river/reservoir and recreational water (Gharpure et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The relative contribution of foodborne transmission in parasitic infections was poorly studied, but recent studies of meta-analysis of risk factors for parasitic infections identi ed the consumption of unwashed vegetables as a relevant risk factor for infection [45,48]. In this context, we wanted to investigate occurrence of protozoan in leafy greens in Morocco.…”
Section: Discussionmentioning
confidence: 99%
“…The association of cryptosporidiosis with raw milk was significant for both mixed population and children. Associations with cryptosporidiosis were observed for barbecued foods, meat of non-specified origin, except beef, dishes prepared outside the home and raw milk [129]. In a retrospective study, eating raw foods was found to increase Cryptosporidium infection prevalence in China, despite the absence of reports of foods contaminated with Crysporidium oocysts in the country [127].…”
Section: Cryptosporidium In Foodmentioning
confidence: 97%
“…The association of dishes prepared outside the home and barbecued foods with infections by Cryptosporidium spp. can be linked to contamination by an infected handler during the preparation [129].…”
Section: Cryptosporidium In Foodmentioning
confidence: 99%
See 1 more Smart Citation